Culturally Embedded Measurement of Latino Caregivers' Engagement in Head Start: A Tale of Two Forms of Engagement. Issue 4 (19th May 2018) - McWayne, Christine; Foster, Brandon; Melzi, Gigliana
ABSTRACT: Practice and Policy : The preschool years represent a critical time to foster family engagement in education for children growing up in poverty. Yet the ways in which Latino families with lower levels of income engage with their children's education at home and at school might look different from how middle-income parents from the dominant U.S. culture do, depending on cultural values and beliefs about best ways to support children's learning as well as on socioeconomic realities that present barriers for traditional forms of engagement. This study sought to examine further the psychometric functioning of a promising new measure of family engagement, developed with and for Latino Head Start families. Research Findings : Results of this study supported continued use of this measure, with clear caveats and directions for future research. Findings suggested that the ways Latino Head Start parents engage with children's learning and development at home (e.g., supporting children's social awareness and behavior, connection to cultural heritage, academic skills) might be a more culturally nuanced and salient form of engagement, while school-based engagement (e.g., volunteering at school, communicating with teachers) might be a more universal form. Findings contribute to understandings of Latino family engagement as well as to methodological considerations for culture-specific measurement development efforts, with relevance for early education researchers and professionals.